1981
DOI: 10.1139/o81-077
|View full text |Cite
|
Sign up to set email alerts
|

Tissue distribution of sulfolipids in the rat. Restricted location of sulfatoxygalactosylacylalkylglyerol

Abstract: Eleven rat tissues (excluding brain) have been assayed for their ability to synthesize sulfatoxygalactosylacylalkylglycerol (SGG) from Na235SO4 in vivo. These tissues were also assayed for the presence of SGG by an indirect immunofluorescence procedure using rabbit anti-SGG and frozen tissue sections. By both procedures SGG was found to be restricted to the testis; several novel sulfolipids were detected during this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1988
1988
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 4 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…In addition, SGC is the major glycolipid of the human endometrium which varies during the menstrual cycle (Kubushiro et al, 1989). SGC is also a significant fraction of the glycolipid of the kidney, brain, and gastrointestinal tract (Lingwood et al, 1981;Murray et al, 1980). We have previously isolated a plasma membrane sulfoglycolipid binding protein, termed SLIP 1, from rat testicular germ cells by SGG affinity chromatography (Lingwood, 1985).…”
mentioning
confidence: 99%
“…In addition, SGC is the major glycolipid of the human endometrium which varies during the menstrual cycle (Kubushiro et al, 1989). SGC is also a significant fraction of the glycolipid of the kidney, brain, and gastrointestinal tract (Lingwood et al, 1981;Murray et al, 1980). We have previously isolated a plasma membrane sulfoglycolipid binding protein, termed SLIP 1, from rat testicular germ cells by SGG affinity chromatography (Lingwood, 1985).…”
mentioning
confidence: 99%
“…In the ileal sections, SGC is expressed in the villus crypts from normal mice. SGC is a major GSL in the mouse kidney (Lingwood et al, 1981), but ΔF508CFTR-transgenic mouse kidney showed no SGC. These results showed that there are dramatic changes of SGC expression in CFTR defective mice.…”
Section: Resultsmentioning
confidence: 99%
“…"SGG was prepared in vitro from PAP35S by use of the renal galactolipid sulfotransferase (Taylor et al, 1987) since this tissue contains no endogenous SGG (Lingwood et al, 1981), yet GG remains a n effective substrate in vitro (Lingwood, 1985~). "SGC was prepared by using the testicular enzyme for a similar reason.…”
Section: Discussionmentioning
confidence: 99%
“…GG was prepared from SGG by anchimeric assisted solvolysis (Lingwood et al, 1983). SGG was deacylated by mild basic hydrolysis (Lingwood et al, 1981) GC and SGC were purchased from Sigma (St. Louis, MO). GM, and GM, gangliosides were kindly provided by Dr. A. Novak, Department of Neurosciences, Hospital for Sick Children.…”
Section: Methodsmentioning
confidence: 99%